IMPACT OF NANOFLUIDS ON EXTERNAL AND INTERNAL FLOW VIA NAVIER-STOKES AND CONVECTIONDIFFUSION EQUATIONS FOR PARALLEL PLATES WITH SLIP BOUNDARY CONDITIONS - Costa, R. C. S. M.; Curi, M. F. (Revista de Engenharia Térmica, 2021)
With the modernization and miniaturization of equipment and systems to increase the overall efficiency in smaller spaces, new cooling solutions need to be developed. Microfluidic in the last decades becomes a new way to get this. Nanofluids are used to attend this demand to optimize efficiency, with their improved thermohydraulic properties, especially different thermal conductivities. To determine the advantages of using a nanofluid for thermal exchange, the properties, parameters and modelling will be presented, and the differential equations necessary to obtain the results. In that sense, the basic theory of fluid mechanics and heat transfer, through the Navier-Stokes and Convection-Diffusion equation, is used in the two-dimensional steady-state formulation. Slip boundary conditions for the velocity field. Constant heat flux and constant temperature at the surface are used for the temperature field, initially without the flow’s microscale effects. The external flow over a flat plate and internal flow between parallel plates will be studied. Considering a laminar flow, with the base fluid being water and engine oil, with various volumetric fractions of Single Wall and Multiple Wall Carbon Nanotubes. To determine the results and create the comparative graphs, the Wolfram Mathematica v.11 software will be used for solving the remaining partial differential equations.